Nanotechnology applied to bio-encapsulation of pesticides - Grillo, Renato [UNESP]; Abhilash, Purushothaman Chirakkuzhyil; Fraceto, Leonardo Fernandes [UNESP] (American Scientific Publishers, 2016)
In recent years, many efforts have been made towards the application of nanotechnology in sustainable food production. In this context, the bio-encapsulation process has taken prominence in particular as an ecofriendly method for pest control while reducing the pesticide load in the environment considerably. By taking into consideration, here we are presenting an overview regarding the prospects for the development of nanoencapsulated pesticides in sustainable agriculture and highlight some challenges to be addressed in order to develop efficient nano-carrier systems that may arise as an alternative for conventional pesticide application. However, much research has to be done in this area in order to develop safe and promising pesticide delivery systems for increasing global food production by enhancing the selectivity, specificity and longevity of the encapsulated pesticides while reducing the negative environmental impacts to ecosystem and human beings.
Keywords: Carrier systems; Environmental nanotechnology; Nanobiotechnology; Pesticides; Sustainable agriculture